Assessment models for telemedicine services in national health systems. (9th September 2008) - Masella, Cristina; Zanaboni, Paolo
Nowadays, decision makers of all national health systems have to correctly assess telemedicine services in order to take responsible decisions on the their adoption into the routine clinical practice. Since the 90s, a wide range of applications were tested, but evidence of benefits is still quite lacking. Scientific literature is mainly characterised, from the one hand, by few relevant theoretical studies which deepen the assessment dimensions or suggest guidelines about the implementation process. From the other hand, empirical and well-designed studies are generally focused on a single dimension, lacking in giving a comprehensive appraisal of the application. As consequence, the aim of this research consists, first of all, in presenting a complete framework that links the main assessment dimensions to the phases of the assessment process. Secondarily, the framework has to be supported by a good empirical analysis and a systematic methodological approach in order to support decision making.